'Pentecost with signs': historical and theological reflections on Spirit baptism from a British and wider European perspective. Issue 2 (2nd July 2020) - Frestadius, Simo
ABSTRACT: Baptism in the Holy Spirit has been central to classical Pentecostal traditions, but its ongoing importance in Pentecostal theology and practice is increasingly questioned. This article explores the common three ideas associated with the classical Pentecostal doctrine, namely, the beliefs that it is (1) a subsequent experience to conversion, (2) accompanied by tongues as initial evidence and (3) given for the purpose of empowerment for witness. The article does so by looking at the broader nature, signs, and purpose of Spirit baptism from a British and wider European classical Pentecostal perspective. The underlying argument is that the fullness of the Spirit experienced by the first generation of Pentecostals in Europe seems to have been spiritually deeper, theologically richer, and practically more inclusive than stated by some of the later doctrinal articulations. This has important theological implications for contemporary formulations of the Pentecostal doctrine of Spirit baptism.